Asian Women And The Hardcore Scene - Indra Sukma Wijaya; Muhammad Andra Setia Putra; Khaerudin Imawan; Dedet Erawati (Al-Makki Publisher, 2024)
This research aims to find out how media framing and the impact obtained from media framing on the representation of women in the hardcore punk scene. This research reveals how media framing affects people's perceptions and understanding of women's representation in the hardcore punk scene and the impact of media framing on women's representation. The many roles of women in the hardcore scene, with the presence of female musicians and fans who actively contribute and bring new perspectives that enrich this music scene. This study uses a qualitative method to describe how media framing represents women in the hardcore punk scene through the website and social media use your voice using Robert N. Entman's framing analysis theory. As for the results of this study, women in the hardcore punk scene are faced with various obstacles and discrimination that must be addressed immediately through concrete actions to improve representation and gender equality in the hardcore punk scene.